Tests of neutrino interaction models with the MicroBooNE detector - Rafique, Aleena (Kansas State University, 2018)
I measure a large set of observables in inclusive charged current muon neutrino scattering on argon with the MicroBooNE liquid argon time projection chamber operating at Fermilab. I evaluate three neutrino interaction models based on the widely used GENIE event generator using these observables. The measurement uses a data set consisting of neutrino interactions with a final state muon candidate fully contained within the MicroBooNE detector. These data were collected in 2016 with the Fermilab Booster Neutrino Beam, which has an average neutrino energy of 800 MeV, using an exposure corresponding to 5.0 x 10¹⁹ protons-on-target. The analysis employs fully automatic event selection and charged particle track reconstruction and uses a data-driven technique to separate neutrino interactions from cosmic ray background events. I find that GENIE models consistently describe the shapes of a large number of kinematic distributions for fixed observed multiplicity, but I show an indication that the observed multiplicity fractions deviate from GENIE expectations.
Keywords: Neutrino interactions; Neutrino detectors; Testing models; Data analysis